A Rare Occurrence of Pulmonary Alveolar Proteinosis after Lung Transplantation - Albores, Jeffrey; Seki, Atsuko; Fishbein, Michael C.; Abtin, Fereidoun; Lynch, Joseph P., III; Wang, Tisha; Weigt, S. Samuel (Seminars in Respiratory and Critical Care Medicine, 2013)
We present a case of pulmonary alveolar proteinosis (PAP) initially diagnosed 28 months after left single-lung transplantation for idiopathic pulmonary fibrosis. The diagnosis was based upon the presence of periodic acid-Schiff (PAS)-positive and surfactant immunostain–positive acellular lipoproteinaceous material within alveoli seen on transbronchial biopsy as well as in bronchoalveolar lavage fluid. The patient eventually also displayed a characteristic “crazy paving” pattern on radiographic imaging. Granulocyte macrophage-colony stimulating factor antibodies were negative, consistent with secondary PAP. PAP is a rare interstitial lung disease with only a few reported cases occurring after lung transplantation. The etiology is thought to be related to a defect in macrophage function caused by immunosuppression. Reduced immunosuppression has been associated with stabilization, but not reversal, of the condition in the case reported here. PAP is an exceptionally rare cause of dyspnea and radiographic infiltrates after lung transplantation and may be related to toxicity of immune-suppressive medications.
Keywords: lung transplantation; pulmonary alveolar proteinosis; interstitial lung disease; immunosuppression